Physiological Mechanism of Exogenous 5-Aminolevulinic Acid Improved the Tolerance of Chinese Cabbage (Brassica pekinensis L.) to Cadmium Stress - Yang, Lijing; Wu, Yue; Wang, Xiaomin; Lv, Jian; Tang, Zhongqi; Hu, Linli; Luo, Shilei; Wang, Ruidong; Ali, Basharat; Yu, Jihua (Frontiers in Plant Science, 2022)
5-aminolevulinic acid (ALA), a new type of plant growth regulator, can reliease the toxicity of cadmium(Cd) to plants. However, the mechanism of ALA involved in plant tolerace to Cd stress has not been thoroughly studied. In the study, ALA roles were investigated in Chinese cabbage (Brassica pekinensis L.) seedlings grown hydroponically in climate box under 50 μM Cd and 25 mg/L of foliar applied ALA. Compared with the control, Cd stress can reduce plant biomass and photosynthetic parameters, but increase MDA and H2O2 content. Compared with the Cd treatment alone, the application of ALA increased the plant biomass and photosynthetic parameters. In addition, compared with single Cd treatment, ALA also reduced the content of MDA and H2O2 by enhancing the antioxidant enzymes activities in ascorbate-glutathione cycle (AsA-GSH) cycle. Compared with the single Cd stress, ALA and Cd co-treatment significantly reduced the Cd content of cabbage seedlings. Further results showed that ALA significantly down-regulates the expressions of Cd absorption and transport related genes in shoots (HMA2, HMA4) and roots (IRT1, IRT2, Nramp1, Nramp3). Taken together, these findings suggest that Cd stress can reduce the plant biomass, aggravate plant oxidative damage and enhance the expression of absorption and transport genes , and which further decreases plant absorption of Cd in cabbage. The exogenous of ALA alleviate Cd stress through affecting antioxidant system,down-regulateing the expression of transport genes, and reduce the content of Cd in Chinese cabbage.